2016
DOI: 10.3389/fmed.2016.00002
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiological Factors in the Relationship between Chronological Age and Calculated Lung Age as Detected in a Screening Setting in Community-Dwelling Subjects

Abstract: AimTo explore the relationship between pathophysiological factors and premature lung aging in a cohort of community-dwelling subjects in a health-screening setting.Methods16,107 pharmacy customers in Germany (5954 males, 10,153 females; mean age 59.7 years) participated in a lung function screening project by providing demographic data, including smoking status and known airway conditions and performing spirometry with a Vitalograph, a spirometry screening device. Lung age was calculated from the spirometric f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…Based on a cohort of 1770 pharmacy customers with common cold purchasing a combination product containing 200 mg ibuprofen and 30 mg pseudoephedrine, we have shown overall efficacy and tolerability data that are comparable to those from placebo-controlled studies. This and previous studies 22 show that surveys among pharmacy customers can be a valuable source of scientific information, particularly for over-the-counter products. Treatment effects of the tested combination product are independent of gender and body weight of the patient and similar across age groups.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Based on a cohort of 1770 pharmacy customers with common cold purchasing a combination product containing 200 mg ibuprofen and 30 mg pseudoephedrine, we have shown overall efficacy and tolerability data that are comparable to those from placebo-controlled studies. This and previous studies 22 show that surveys among pharmacy customers can be a valuable source of scientific information, particularly for over-the-counter products. Treatment effects of the tested combination product are independent of gender and body weight of the patient and similar across age groups.…”
Section: Discussionsupporting
confidence: 68%
“…We also found data collection among pharmacy customers to be a scientifically valuable source of information in a previous airway project. 22 The main advantages of such approach are that it can recruit a very broad, representative real life population with little restriction of inclusion/exclusion criteria and much larger numbers of patients than typically can be included in a classic randomised trial. These large numbers allow applying multiple regression approach to identify variables associated with positive treatment outcomes.…”
Section: Factors Associated With Greater Treatment Efficacymentioning
confidence: 99%
“…However, we deem this setting suitable to obtain real-world evidence for over-the-counter medications. Moreover, our previous work using other airway-related over-the-counter medications has demonstrated the external validity of this approach for generating real-world evidence for non-prescription medicines [19, 20]. …”
Section: Discussionmentioning
confidence: 99%
“…The values of ∆LA are somewhat different, which may partly be caused by using different prediction equations for estimating SLA. Furthermore, Kardos et al (2016) reported that being a smoker was one of the most important factors related to higher SLA. They also noted that SLA was a useful method for monitoring the lung function of individuals with different smoking status.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Kardos et al. (2016) reported that being a smoker was one of the most important factors related to higher SLA. They also noted that SLA was a useful method for monitoring the lung function of individuals with different smoking status.…”
Section: Discussionmentioning
confidence: 99%